GENE-42. THE GENOMIC LANDSCAPE OF TRIPLE-NEGATIVE GLIOBLASTOMA. (5th November 2018) - Diplas, Bill; Waitkus, Matthew; He, Xujun; Brosnan-Cashman, Jackie; Liu, Heng; Chen, Lee; Wang, Zhaohui; Moure, Casey; Killela, Patrick; Lipp, Eric; Rodriguez, Fausto; Jiao, Yuchen; et al.
Abstract: Glioblastoma (GBM) is the most common and deadly primary malignant brain tumor in adults. Mutations in the TERT promoter ( TERTp ) and isocitrate dehydrogenase 1 or 2 ( IDH1/2 ) can classify 80% of GBMs into molecular subgroups with distinct clinical courses. These molecular subgroups utilize distinct genetic mechanisms of telomere maintenance, either TERTp mutation leading to telomerase activation or ATRX -mutation leading to an alternative lengthening of telomeres phenotype (ALT). However, approximately 20% of GBMs lack alterations in TERTp and IDH1/2 . These tumors, designated TERTp WT - IDH WT or triple-negative glioblastomas (as they also lack 1p19q co-deletion) do not have well-established genetic biomarkers or defined mechanisms of telomere maintenance. Here we performed whole-exome, whole-genome, and RNA-sequencing on a cohort of triple-negative GBMs to define their genetic landscape. We discovered recurrent inactivating mutations in SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily A-like 1 ( SMARCAL1 ) in 21% (8/39) of triple-negative GBMs. Using telomere maintenance characterization assays, we show that SMARCAL1 -mutant cases exhibited the ALT phenotype. Using CRISPR/Cas9 gene editing in GBM cell lines, we found that inducing loss of SMARCAL1 generates features of ALT. Rescue of expression of SMARCAL1 in SMARCAL1 -null cell lines markedly suppressed ALT features and was dependent on the enzyme helicase activity. Furthermore, using break-apart FISH and whole genome sequencing, we identified recurrent rearrangements upstream of TERT in 50% of triple-negative GBMs. These TERT -rearranged tumors exhibited elevated levels of TERT mRNA expression. This represents a novel mechanism of telomerase activation in GBMs lacking the well-known TERT promoter hotspot mutations. Finally, we identify recurrent BRAF V600E mutations in younger patients with GBM. Collectively, our findings define novel molecular subgroups of glioblastoma, including a telomerase-positive subgroup driven by TERT -structural rearrangements ( IDH WT - TERT SV, 50%), and an ALT-positive subgroup ( IDH WT -ALT, 40%) with mutations in ATRX or SMARCAL1. We also establish SMARCAL1 inactivating